A Perturbed-Chain SAFT Equation of State Applied to Mixtures of Short- and Long-Chain n‑Alkanes - Nasrifar, Khashayar (American Chemical Society Publication, 2013)
ABSTRACT: A simplified hard-chain dimer theory is employed with perturbed-chain statistical associating fluid theory (PCSAFT) in calculating the vapor pressures and saturated liquid volumes of pure n-alkanes from methane to n-eicosane. Compared to the original PC-SAFT, the developed model is in better agreement with the experimental vapor pressures and saturated liquid volumes of n-alkanes along the vapor−liquid coexistence curve and the critical properties from n-butane toward longer n-alkanes. Predicting the vapor−liquid equilibria (VLE) of binary mixtures containing methane and a long-chain n-alkane, the new model describes the mixtures more accurately than PC-SAFT. With no binary interaction parameter, the model adequately describes the experimental VLE data, in particular, near the critical points. In the prediction of the VLE of mixtures containing ethane, propane, n-hexane, and a long-chain n-alkane, the differences between the two models become less appreciable.